Feasibility study of the reverberant shear wave elastography technique for diabetic foot characterization - Gutiérrez Delgado, Fernando Iván (2020)
The diabetic foot is a complication that stems from diabetes when it is not properly managed. The underlying biomechanical changes that occur inside the plantar tissue as a result of glycation when a person begins to develop this complication suggest that there is a change in its elasticity and hardness. Consequently, these changes could be estimated quantitatively with elastography, which comprises many modalities that can be implemented with a magnetic resonator, an ultrasound equipment, among other devices. One of these modalities relies on the generation of a reverberant shear wave field inside the tissue or medium of interest, called reverberant shear wave elastography (RSWE). In that sense, the literature is scarce pertaining diabetic foot research with ultrasound elastography, while the RSWE modality is still in its early stages. The main objective of this work focuses on assessing the clinical application feasibility of this novel elastography technique by characterizing the elasticity of regions of the foot plant.